2003
DOI: 10.1007/s10144-002-0134-4
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of acorns on the wood mouse Apodemus speciosus

Abstract: Antinutritional effects of acorns and tannic acid on the Japanese wood mouse Apodemus speciosus were examined in the laboratory. The first feeding experiment was conducted for 15 days using three types of diet: control diet (laboratory chow for mice), acorns of Quercus serrata (QS), and acorns of Q. mongolica var. grosseserrata (QM), which differ in tannin content (control, tannin free; QS, 2.7% tannic acid equivalent; QM, 8.5%). Six and one of eight mice died in the QM and QS groups, respectively, whereas all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 67 publications
5
59
2
1
Order By: Relevance
“…As described by Shimada and Saitoh (2003), one of the eight mice died in the QS group. In the present study, we conducted further analyses only on the individuals that survived until the end of the experiment in order to investigate the successive changes in the effects of acorn ingesting (for the control and QS groups, n = 8 and 7, respectively).…”
Section: Feeding Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As described by Shimada and Saitoh (2003), one of the eight mice died in the QS group. In the present study, we conducted further analyses only on the individuals that survived until the end of the experiment in order to investigate the successive changes in the effects of acorn ingesting (for the control and QS groups, n = 8 and 7, respectively).…”
Section: Feeding Experimentsmentioning
confidence: 99%
“…Wood mouse responses to acorn tannins 209 Shimada and Saitoh (2003) revealed that A. speciosus fed QS acorns suffered severe damage because of reduced dry matter intake and nitrogen digestibility. The present experiment, however, showed that the negative effects of the acorns decreased through continuous ingesting of acorns.…”
Section: Induction Of Prpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding Experiments In order to examine the relationships between dietary tannin and fecal proline, we performed feeding experiments using a powdered formula diet that had a nutritional composition similar to that of acorns of Quercus crispula and Quercus serrata in terms of all major constituents except tannins (hereafter referred to as the basal diet; see details in the work of Shimada and Saitoh 2003). Tannic acid (Wako Pure Chemical Industries) was added to the basal diet at 1, 2, 3, or 4% on a dry weight basis (hereafter referred to as the 1-4% TA diets).…”
Section: Methodsmentioning
confidence: 99%
“…Tannins are a widespread group of PSMs that are broadly distributed in various plant parts (Waterman and Mole 1994). Ingesting tannins, a diverse group of watersoluble phenolics with high affinity for proteins, may have negative effects on herbivores, such as reduction in protein digestibility (Robbins et al 1987;Chung-MacCoubrey et al 1997;Shimada and Saitoh 2003), damage to the gastrointestinal mucosa and epithelium (Meiser et al 2000), or endogenous nitrogen loss (Shimada and Saitoh 2003).…”
Section: Introductionmentioning
confidence: 99%